Implementasi CITES (Convention on International Trade in Endangered Species of Wild Fauna and Flora) dalam Menangani Perdagangan Kukang Ilegal di Indonesia - Wahyadyatmika Permana Adi; Reni Windiani; Nadia Farabi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
Slow loris or Nycticebus sp is one of endemic primate animals in Indonesia. Since 2007, slow loris has been categorized into Appendix I CITES (Convention on International Trade in Endangered Species of Wild Fauna and Flora). It means that slow loris is threatened to extinction, so this species cannot be used as a commodity on commercial trade. In fact, the number of slow loris in Indonesia, specifically on Sumatra island still continue decreased from 2007-2014. Even though, Indonesia has ratified CITES which is explained on UU No. 5 Tahun 1990 relates to Conservation of Natural Resources and Ecosystems. Through this regulation, Indonesia spreads and delegates an authority to implement CITES on Ministry of Environment and Forestry as management authority and Research Center for Biology-LIPI as scientific authority. This paper aims to analyze to what extent the compliance of Indonesia on CITES regime and determine main factors that cause trade of slow loris in Indonesia. To achieve these objectives, it is used a qualitative method through literature reviews and policy documents, then, it compared with compliance theory and public policy implementation. The findings of this paper shows that Indonesia has respect and compliant to CITES. Indonesia compliant CITES to achieve the national interest, especially in the protection of slow loris. However, slow loris trading still occurs due to several factors, such as lack of bureaucratic structure, lack of communication, less of resources quality and quantity, and disposition. In addition, a partnership and bilateral agreement among Indonesia and other country to minimize slow loris trading is still unsuccessful.